2022
DOI: 10.1177/03635465211063901
|View full text |Cite|
|
Sign up to set email alerts
|

Risk Factors for Failure After Osteochondral Allograft Transplantation of the Knee: A Systematic Review and Exploratory Meta-analysis

Abstract: Background: Graft failure after osteochondral allograft transplantation (OCA) of the knee is a devastating outcome, often necessitating subsequent interventions. A comprehensive understanding of the risk factors for failure after OCA of the knee may provide enhanced prognostic data for the knee surgeon and facilitate more informed shared decision-making discussions before surgery. Purpose: To perform a systematic review and meta-analysis of risk factors associated with graft failure after OCA of the knee. Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 42 publications
0
42
3
Order By: Relevance
“… 61 A more recent systematic review and meta-analysis of 16 studies totaling 1401 patients by Kunze et al found that bipolar defects of the patellofemoral or tibiofemoral articulating surfaces, male sex, older age, and greater BMI were significantly associated with an increased failure rate after OCA transplantation. 17 Chondral size defect or location, patellar defects, and concomitant procedures were not associated with increased risks of failure, which were in contrast to other studies. 17 , 24 , 61 , 63 In a retrospective study, sex mismatch between donor and recipient was associated with a 3-times greater likelihood to fail at 5 years compared to same-sex transplantation.…”
Section: Risk Factors For Failurecontrasting
confidence: 57%
See 3 more Smart Citations
“… 61 A more recent systematic review and meta-analysis of 16 studies totaling 1401 patients by Kunze et al found that bipolar defects of the patellofemoral or tibiofemoral articulating surfaces, male sex, older age, and greater BMI were significantly associated with an increased failure rate after OCA transplantation. 17 Chondral size defect or location, patellar defects, and concomitant procedures were not associated with increased risks of failure, which were in contrast to other studies. 17 , 24 , 61 , 63 In a retrospective study, sex mismatch between donor and recipient was associated with a 3-times greater likelihood to fail at 5 years compared to same-sex transplantation.…”
Section: Risk Factors For Failurecontrasting
confidence: 57%
“…Contraindications for OCA transplantation include uncorrected limb malignment and/or ligamentous instability, body mass index (BMI) >35 kg/m 2 , smoking, alcohol abuse, chronic steroid use, advanced osteoarthritis within any compartment (Kellgren-Lawrence grade >2), and systematic autoimmune or inflammatory joint disease ( Table 1 ). 2 , 17 Bakay et al found in their study that all grafts with unaddressed 10°–15° varus malalignment after OCA transplantation failed in the short-term at a mean follow-up of 19 months. 18 Other groups have similarly reported that uncorrected coronal malalignment is a risk factor for failure that can result in an almost seven times higher failure rate.…”
Section: Patient Selection and Contraindicationsmentioning
confidence: 96%
See 2 more Smart Citations
“… 1 , 7 , 18 While the provided evidence does not allow for a reliable conclusion of parameters influencing the outcome of OCF fixation, studies investigating osteochondral allograft transplantation (OCA) and osteochondral autograft transplantation have consistently reported increasing age as a risk factor for graft failure. 17 , 33 In addition, there is an unmet need for imaging studies evaluating postoperative cartilage quality and progression of disease after the fixation of OCFs.…”
mentioning
confidence: 99%